ANALISIS MESIN PENCARIAN GOOGLE SCHOLAR SEBAGAI SUMBER BARU UNTUK KUTIPAN - Ageng Setiani Rafika; Hanifah Yunan Putri; Fitroh Diah Widiarti (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2017)
In the modern era such as the current quality of the scientific articles are very abundant and diverse. In 2004 Google gives the new innovation with the presence of Google Scholar. Google Scholar is a service that allows users to search for scientific articles or journals in the form of text of various publication formats one of which is a PDF, which aims to let users more easily get the idea or the idea to make a quality scientific work. Google Scholar can produce a scientific article or journal every day. And every scientific article that contained quotes from people who made the article that users could use as a reference in the making of a scientific article or journal. The method used in this research is by literature study, where the existing data into an information that is easily understood and useful. In the method of SWOT one of them provide convenience for users to find information quickly with a matter of seconds in Google Scholar. The research also uses Flowchart and Prototype which shows every step of the program or procedure in the right order and has a basic description when the user uses Google Scholar.